Epidemiological Study of Thoracolumbar Pott’s Spine at a Tertiary Care Hospital in North India - Asheesh Kumar Gupta; Aditya Srivastava; R. L.S. Sengar (Romanian Neurosurgery, 2018)
The vertebral column is involved in less than 1% of all the cases of tuberculosis. It can associated with major neurological deficits due to compression of adjacent neural structures with significant deformity of spinal column. Therefore, early diagnosis and management of spinal TB has special importance in preventing these serious complications. In order to extract current trends in diagnosis and medical or surgical treatment of spinal TB we performed a review with patients admitted to our hospital between 2016 and 2017. Although the development of more accurate imaging modalities such as magnetic resonance imaging and advanced surgical techniques have made the early diagnosis and management of spinal TB much easier, these are still very challenging topics. In this review we aim to discuss the diagnosis and management of spinal TB based on studies with acceptable design, clearly explained results and justifiable conclusions.